Assessing ergonomic risks of software: Development of the SEAT. (March 2017) - Peres, S. Camille; Mehta, Ranjana K.; Ritchey, Paul
Abstract: Software utilizing interaction designs that require extensive dragging or clicking of icons may increase users' risks for upper extremity cumulative trauma disorders. The purpose of this research is to develop a Self-report Ergonomic Assessment Tool (SEAT) for assessing the risks of software interaction designs and facilitate mitigation of those risks. A 28-item self-report measure was developed by combining and modifying items from existing industrial ergonomic tools. Data were collected from 166 participants after they completed four different tasks that varied by method of input (touch or keyboard and mouse) and type of task (selecting or typing). Principal component analysis found distinct factors associated with stress ( i.e., demands) and strain ( i.e., response). Repeated measures analyses of variance showed that participants could discriminate the different strain induced by the input methods and tasks. However, participants' ability to discriminate between the stressors associated with that strain was mixed. Further validation of the SEAT is necessary but these results indicate that the SEAT may be a viable method of assessing ergonomics risks presented by software design. Highlights: Translating biomechanics knowledge to evaluate ergonomic risks of software is novel. We developed the Self-report Ergonomic Assessment Tool (SEAT) to assess ergonomic risks of software interaction methods. SEAT offered response consistency and discriminant validity. SEAT needs to be validated using biomechanical and physiological responses.